Investigation of Flame Characteristics of a Flameless Combustor Ignition System Using Direct Nozzle - RUSTU, MUHAMMAD NORFIRDAUS; KASANI, ADAM (Progress in Engineering Application and Technology, 2023)
In many industries, a combustor is used to generate heat to dry or shrinking process. The ignition system for a combustor is necessary to make sure the flame can stay and generate heat during process. The failed of ignition during firing up the flame during pre-heating is the problem that industry are facing is the main problem that need to be solve. So, the need to study flame characteristics using direct nozzle is necessary to confront the problem This study has conducted an experiment using direct nozzle in order to study the flame characteristics and the maximum temperature. The result of this study shows that at equivalence ratio of 1.67, the flame length is acceptable to be used in combustion process. Besides, the flame temperature is steady along the experimental record time. As a result, the used of direct nozzle is not recommended because there is a little bit of flame lift of during the experiment. This experiment can be used to find a suitable nozzle for a combustor.